The feasibility and efficiency for constructing arteriovenous fistula with <2 mm vein—a systematic review and meta-analysis - Feng, Ruijia; Wang, Siwen; Yu, Jianwen; Zheng, Xunhua; Chen, Wei; Wang, Xin; Chang, Guangqi (Frontiers in Cardiovascular Medicine, 2023)
Background: Autogenous arteriovenous fistula (AVF) is an efficient hemodialysis access for patients with end-stage kidney disease (ESKD). The specific threshold of vein diameter still not reached a consensus.We conducted a comprehensive search in PubMed, Embase, and Web of Science databases for articles which comparing the treatment outcomes of AVF with 2mm as vein diameter threshold. Fixed and random effect model were used for synthesis of results. Subgroup analysis was designed to assess the risk of bias.Result: 8 high-quality articles were included finally. Among a total of 1075 patients (675 males and 400 females), 227 and 809 patients possessed <2mm and ≥2mm vein respectively. Apart from gender and coronary artery disease (P<0.05), there was no significant difference in age, diabetes, hypertension or radial artery between maturation and non-maturation groups. The functional maturation rate was lower in patients with <2mm vein according to fixed effect model (OR=0.19, 95%CI [0.12, 0.30], P<0.01).There was no significant difference in primary (OR=0.63, 95%CI [0.12, 3.25], P=0.58) or cumulative patency rates (OR=0.40, 95%CI [0.13, 1.19], P=0.10).Vein diameter less than 2mm has a negative impact on the functional maturation rate of AVF, while it does not affect the primary and cumulative patency rates (12 months).